Neural oscillations induced by gamma sensory entrainment in cognitive biotype of depression - Shi, Xiaoning; Wang, Hongli; Zhao, Yingying; Wang, Chenyang; Qi, Yongsheng; Gao, Michel; Wei, Mengping; Wang, Gang (Frontiers in Psychiatry, 2025)
AimAbnormal neural oscillations have long been associated with cognition in depression, especially gamma oscillation that participates in neurocircuit function, emotion, and cognition. However, whether gamma sensory entrainment induces alterations in neural oscillations within the cognitive biotype of depression remains unresolved.MethodThe study includes 141 depressed patients in remission. We used Measurement and Treatment Research to Improve Cognition in Schizophrenia (MCCB) to identify the cognitive biotype in depression. Gamma sensory entrainment and spectral power were conducted through Electroencephalogram (EEG). Furthermore, we did correlation analysis to explore the relationship between neural oscillations induced by gamma entrainment with cognitive function in depression.ResultsWe enrolled 141 depressed patients in remission, 56 were identified as cognitive biotype. We found that alpha power caused by gamma entrainment with 37 and 48 Hz decreased in cognitive biotype. Specifically, alpha power induced by 37 Hz gamma entrainment decreased alpha power in P3 (t =-2.394, FDR = 0.049), P4 (t =-2.713, FDR = 0.038), Fp1 (t =-2.530, FDR = 0.048), T3 (t =-2.689, FDR = 0.038), T5 (t =-2.341, FDR = 0.049), F7 (t =-2.438, FDR = 0.049), T4 (t =-2.764, FDR = 0.038) and Pz (t =-2.691, FDR = 0.038) channels in cognitive biotype. While alpha power caused by 48 Hz gamma entrainment showed decreased alpha power only in T4 channel (t =-3.135, FDR = 0.04) except other channels in cognitive biotype. Moreover, alpha oscillation induced by 37 Hz gamma entrainment was correlated with working memory in P3, P4, Fp1, T3, T5, F7, T4 and Pz channels; problem solving-ability in T5 channel. Alpha oscillation caused by 48 Hz gamma entrainment showed significant correlation with working memory, problem solving-ability and total scores in T4 channel. Furthermore, we observed that the most optimum stimulus frequency of gamma entrainment eliciting peak responses varied among participants.ConclusionOur results confirmed the influence of gamma entrainment by sensory stimuli on neural activity in cognitive biotype of depression, and abnormal alpha power was associated with cognitive function. Furthermore, gamma sensory entrainment with the most optimum stimulus frequency could serve as a potential method to improve cognition in cognitive biotype of depression.